Evidence for the decay D-0 -> K+pi(-)pi(+)pi(-) - Dytman, SA; Savinov, V; Chen, S; Hinson, J; Lee, J; Miller, D; Shibata, E; Shipsey, I; Pavlunin, V; Cronin-Hennessy, D; Lyon, A; Park, W; et al. (2001)
We present a search for the "wrong-sign" decay D0→K+π-π+π - using 9 fb-1 of e+e- collisions on and just below the Y(4S) resonance. This decay can occur either through a doubly Cabibbo-suppressed process or through mixing to a D̄0 followed by a Cabibbo-favored process. Our result for the time-integrated wrong-sign rate relative to the decay D0→K-π+π-π + is (0.0041-0.0011+0.0012(stat)±0.0004(syst)) ×(1.07±0.10)(phase space), which has a statistical significance of 3.9 standard deviations.